Answer:
212
Step-by-step explanation:
<u>Rule</u>
- Subtract the 2nd number from the first to obtain the first digit(s) of the answer.
- Add the 2nd number to the 1st to obtain the last digit(s) of the answer.
5 - 3 = 2
5 + 3 = 8
Therefore: 28
9 - 1 = 8
9 + 1 = 10
Therefore: 810
8 - 7 = 1
8 + 7 = 15
Therefore: 115
6 - 2 = 4
6 + 2 = 8
Therefore: 48
7 - 5 = 2
7 + 5 = 12
Therefore: 212
Answer:
17/6
Step-by-step explanation:
The explicit rule for the arithmetic sequence is a(n) = 7n + 8 if the arithmetic series is 15, 22, 29,...
<h3>What is a sequence?</h3>
It is defined as the systematic way of representing the data that follows a certain rule of arithmetic.
We have:
In the first week, only 15 shirts were sold. In the next week, 22 shirts were sold and in the third week, 29 shirts were sold.
15, 22, 29,...
The first term a = 15
The common difference d = 22 - 15 = 7
a(n) = 15 + (n - 1)7
a(n) = 7n + 8
Thus, the explicit rule for the arithmetic sequence is a(n) = 7n + 8 if the arithmetic series is 15, 22, 29,...
Learn more about the sequence here:
brainly.com/question/21961097
#SPJ1
It is 3/2 • 3/4 because you have to make the mixed number an improper fraction. Theb you would solve 3/2 • 3/4 and get 9/8 and that simplified is 1 1/8
Answer:
(x, y) = (2 2/9, -1 4/9)
Step-by-step explanation:
Equate the values of y and solve for x.
1/4x -2 = -2x +3
(2 1/4)x = 5 . . . . . . . . add 2+2x to both sides
x = 20/9 = 2 2/9 . . . multiply by 4/9
y = -2(2 2/9) +3 = -4 4/9 +3 . . . . substitute for x in the second equation
y = -1 4/9
The solution is x = 2 2/9, y = -1 4/9.